Impact of Financial Compensation on the Performance of Marketing Employees - Achmad Daengs Gatot Soeherman; Enny Istanti; I Gede Wiyasa (Yayasan Adra Karima Hubbi, 2025)
Background. Compensation is one of the key aspects in determining employee performance. It becomes a critical concern for companies, as employees strive to achieve the performance standards set by the organization. Recognizing the importance of compensation in supporting performance, compensation management should be a top priority. Purpose. Timeliness and the amount of compensation provided by the company significantly influence employees’ work spirit, motivation, job performance, and overall performance. The absolute income level of employees determines their standard of living, while relative income reflects their social status and dignity. Method. Therefore, if employees perceive that the compensation they receive is inadequate, their work spirit, motivation, job performance, and overall performance may drastically decline. Results. Motivation is a condition that drives employees in a focused and goal-oriented manner to achieve company objectives. Work performance is essential for business progress since the success or failure of a business is significantly influenced by employee performance. Conclusion. The financial compensation variable (X) has a positive influence on the employee performance variable (Y) with a coefficient of 0.402. The positive coefficient indicates a direct relationship between financial compensation and employee performance. This means that any change in the financial compensation variable by one unit will result in a 0.402 change in the employee performance variable, assuming other independent variables remain constant.